2019
DOI: 10.15673/fst.v13i4.1562
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Food Pathogens and Determination of Their Distribution Level in Ukrainian Food Products of Animal and Plant Origin by PCR Method

Abstract: The foodborne pathogens cause serious public health problems in each country. In this regard, microbiological investigation is included in food safety management of the food chain. Molecular methods and mostly polymerase chain reaction (PCR) are considered highly sensitive, specific and rapid methods for pathogens detection from raw material and food. This study describes the using of specially designed and highly specific primers for PCR to identify 5 common and especially dangerous causeve agents of food poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…where, [Іn Н] = the concentration of the inhibitor obtained experimentally, and t = the duration of the induction period, s. Microbiological parameters were determined by classical as well as accelerated PCR methods using microbiological media Compact Dry (Nissui Pharmaceutical Co. Ltd., Japan) (Kapreliants et al, 2016;Pylypenko et al, 2017;Berhilevych et al, 2019;Danylova et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…where, [Іn Н] = the concentration of the inhibitor obtained experimentally, and t = the duration of the induction period, s. Microbiological parameters were determined by classical as well as accelerated PCR methods using microbiological media Compact Dry (Nissui Pharmaceutical Co. Ltd., Japan) (Kapreliants et al, 2016;Pylypenko et al, 2017;Berhilevych et al, 2019;Danylova et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Between 2012 and 2015, 97 E. coli isolates (42.2%) were isolated from 230 bacterial samples collected from flushes from beef (130) and swine (100) carcasses obtained from five slaughterhouses in Ukraine, among which seven (7.2%) STEC strains (five beef and two swine carcass swabs) were identified by PCR (Berhilevych et al, 2018). In another study, Shiga toxin-producing E. coli (STEC) was detected in 8.1% and 5.7% of samples collected from beef and swine carcasses, respectively (Berhilevych et al, 2019). It indicates the extreme relevance of STEC monitoring at all stages of livestock production.…”
Section: Escherichiosis (E Coli Including Stec)mentioning
confidence: 99%
“…Currently, some difficulties in identifying STEC serotypes by bacteriological and immunological methods (Baluta et al, 2009;Sukharev, 2011) can be successfully solved using molecular genetic methods (Berhilevych et al, 2014(Berhilevych et al, , 2016(Berhilevych et al, , 2019Kasianchuk et al, 2015). Molecular genetic studies have shown that STEC serovariates of E. coli can be collected from the carcasses of cattle and pigs.…”
Section: Escherichiosis (E Coli Including Stec)mentioning
confidence: 99%